Respuesta :
Step-by-step explanation:
a). Let [tex]x^{2}+y^{2}=4[/tex]
[tex]y^{2}=4-x^{2}[/tex]
Now since [tex]y^{2}[/tex] is a square of an integer, its value is [tex]\geq[/tex] 0.
Therefore, [tex]4-x^{2}[/tex] ≥ 0, since x is an integer
where [tex]4-x^{2}[/tex] = 1,2,3,...
and x = 1
But as x = [tex]\sqrt{2}, \sqrt{3}[/tex],... cannot be integer
∴ [tex]y^{2}=4-x^{2}[/tex]
[tex]y^{2}=4-1[/tex]
[tex]y = \sqrt{3}[/tex]
= 1.732 which is not an integer
Thus, any positive integer cannot be written as the sum of the squares of the two integers.
b). Let n be an integer
∴ [tex]3(n^{2}+2n+3)-2n^{2}[/tex]
On solving we get,
[tex]3n^{2}+6n+9-2n^{2}[/tex]
[tex]n^{2}+6n+9[/tex]
[tex]n^{2}+3n+3n+9[/tex]
[tex]n(n+3)+3(n+3)[/tex]
[tex](n+3)(n+3)[/tex]
[tex](n+3)^{2}[/tex]
which is a perfect square
Hence proved.
Answer:
Step-by-step explanation:
a). Let
Now since is a square of an integer, its value is 0.
Therefore, ≥ 0, since x is an integer
where = 1,2,3,...
and x = 1
But as x = ,... cannot be integer
∴
= 1.732 which is not an integer
Thus, any positive integer cannot be written as the sum of the squares of the two integers.
b). Let n be an integer
∴
On solving we get,
which is a perfect square
Hence proved.